An efficient indexing framework for data dissemination in wireless sensor networks. (October 2020) - Badarneh, Hazem Jihad; Mansoor, Ali Mohammed; Rahman, Anis Ur; Ravana, Sri Devi
Abstract: Wireless Sensor Networks grow rapidly due to the sensing and scanning capabilities of nodes. The sensors are capable to move randomly and send periodic reports, hence they must be processed efficiently. This requirement increases the indexing burden, in particular, indexing the mobile sensors' data. The grid-based indexing techniques in random mobile sensors suffer from high dependability on packet attributes and the necessity of registering the current cluster location of each sensor and assign its destination periodically. Therefore, this work proposes a framework called Dynamic-Coalition to efficiently improve the indexing packets of random mobile sensors. The proposed framework alleviates the disseminated packets by constructing dynamic-coalitions using relevancy-measure. The dynamic-coalition framework is superior in terms of average routing overhead and packet delivery ratio. It can significantly outperform R-tree, Decomposition-tree, and Grid-based DBSCAN with Cluster Forest in terms of index building time overhead, the number of traversed nodes, and space cost overhead.